Syncing the brain’s networks: dynamic functional connectivity shifts from temporal interference - Zhu, Zhiqiang; Tang, Dongsheng; Qin, Lang; Qian, Zhenyu; Zhuang, Jie; Liu, Yu (Frontiers in Human Neuroscience, 2024)
Background: Temporal interference (TI) stimulation, an innovative non-invasive brain stimulation approach, has the potential to activate neurons in deep brain regions. However, the dynamic mechanisms underlying its neuromodulatory effects are not fully understood. This study aims to investigate the effects of TI stimulation on dynamic functional connectivity (dFC) in the motor cortex. Methods: 40 healthy adults underwent both TI and tDCS in a double-blind, randomized crossover design, with sessions separated by at least 48 hours. The total stimulation intensity of TI is 4 mA, with each channel's intensity set at 2 mA and a 20 Hz frequency difference (2 kHz and 2.02 kHz). The tDCS stimulation intensity is 2 mA. Resting-state functional magnetic resonance imaging (rs-fMRI) data were collected before, during, and after stimulation. dFC was calculated using the left primary motor cortex (M1) as the region of interest (ROI) and analyzed using a sliding time-window method. A two-way repeated measures ANOVA (group×time) was conducted to evaluate the effects of TI and tDCS on changes in dFC. Results: For CV of dFC, significant main effects of stimulation type (P = 0.004) and time (P < 0.001) were observed. TI showed lower CV of dFC than tDCS in the left postcentral gyrus (P < 0.001). TI-T2 displayed lower CV of dFC than TI-T1 in the left precentral gyrus (P < 0.001). For mean dFC, a significant main effect of time was found (P < 0.001). TI-T2 showed higher mean dFC than tDCS-T2 in the left postcentral gyrus (P = 0.018). Within-group comparisons revealed significant differences between time points in both TI and tDCS groups, primarily in the left precentral and postcentral gyri (all P < 0.001). Results were consistent across different window sizes. Conclusion: 20 Hz TI stimulation altered dFC in the primary motor cortex, leading to a significant decreasing variability and increasing mean connectivity strength in dFC. This outcome indicates that the 20 Hz TI frequency interacted with the motor cortex's natural resonance.